Association of Klotho Gene Polymorphism with Cerebral Infarction: Klotho Gene Polymorphism in Cerebral Infarction - Li, Yu; Zhang, Qiang; Bao, Haiping; Nie, Chen (Journal of Medical Biochemistry, 2021)
Background: We aimed to investigate the expression of Klotho gene in peripheral blood of patients with cerebral infarction (CI) and the association of its polymorphisms with the occurrence of CI. Methods: A total of 60 CI patients (CI group) and 20 healthy people receiving physical examination (control group) were enrolled as the research subjects. The expression of Klotho gene in CI group and control group was determined using enzyme-linked immunosorbent assay kit. Single nucleotide polymorphisms (rs192031, rs200131 and rs102312) in the promoter region of the Klotho gene were typed via conformational difference gel electrophoresis. Besides, whether the distribution frequencies of Klotho genotypes conformed to Hardy-Weinberg equilibrium was evaluated by chi-square test. Meanwhile, the associations of Klotho alleles and gene polymorphisms with CI occurrence were analyzed. Results: The protein expression level of Klotho in the peripheral blood was remarkably lower in patients in CI group than that in control group (P<0.05). Hardy-Weinberg equilibrium analysis revealed that Klotho gene polymorphisms (rs192031, rs200131 and rs102312) conformed to the genetic equilibrium distribution (P>0.05). Gene-based association analysis manifested that only rs192031 polymorphism and alleles were correlated with CI occurrence (P<0.05). Systolic blood pressure and high-density lipoprotein cholesterol were notably higher in CI patients with TT genotype of Klotho gene polymorphism rs192031 than those in control group (P<0.05). Furthermore, there were no associations of rs200131 and rs102312 polymorphisms and alleles with the occurrence of CI (P>0.05). Conclusions: The expression level of Klotho is evidently reduced in the peripheral blood of CI patients. Rs192031 in the promoter region of the Klotho gene is associated with the occurrence of CI, while rs200131 and rs102312 have no relations with CI.